Model Pemberdayaan dalam Penanggulanan Perilaku Seks Bebas Pelajar di Pacitan - Muhammad Fashihullisan; Martini Martini (LPPM Press, 2014)
The purpose of this study is to analyze the causes of adolescent students who loses hervirginity and do free sex, to analyze supporting factors that make adolescents and studentseasily do free sex, a risk that must be faced by teenagers and students after losing virginityand free sex, to develop a model of prevention and reduction of free sex culture amongstudents. The research shows that the factors that causes loss of virginity in adolescents are:unhealthy courtship factors, influenced values among teenagers, influenced values in theneighborhood. The factors that cause teenagers to have free sex are easy: loss of virginity,condom as avoidance beliefs on sexual risk-free, the availability of cheap hotel serves freesex activity. Risks faced by adolescents after losing virginity include: the risk burden to keepa secret that they was not a virgin, the risk of addiction to repeat the free sex, the risk ofpregnancy so they will be dropped out from school, reproductive health risks. While themodel is a model of free sex prevention outreach to parents, schools, government and societythat sex is a new emerging values established among teenagers.